Story shear distribution of high strength steel frame with D-eccentric braces based on multi-seismic-hazard levels. (February 2023) - shen, Li; Yuting, Gao; Penggang, Tian; Lin, Mu; Junlong, Lu
Abstract: High-strength steel frame with D-eccentric braces (D-HSS-EBF) refer to the link that uses Q355 steel (The yield strength f y ≤ 355 MPa), while the non-energy element, such as column and beam, uses the high-strength steel Q460 or Q690 ( f y = 460 MPa or 690 MPa), which is a new seismic resistant structure. The links developed full plastic deformation when the structure suffered rare earthquakes, to protect the high-strength steel frame. The story shear distribution is not suitable for the capacity-based design method, due to the stiffness of D-HSS-EBF being changed under plastic state. Therefore, this paper presents the elastic–plastic story shear distribution of D-HSS-EBF under various seismic hazard levels, including frequent earthquakes, moderate earthquakes, rare earthquakes and super-rare earthquakes. Based on this, the prototype structures of D-HSS-EBF are designed considering different stories (4-, 8-, 12-, and 16-stories) and different link lengths (900 mm, 1000 mm and 1100 mm), and the story shear distribution modes under various seismic hazard levels are raised under near-fault ground motions and far-fault ground motions. Furthermore, the parameters of story shear distribution under rare earthquakes are determined by the elastic–plastic lateral force. The time history analysis results indicated that the link length has little impact on the story shear distribution, and the near-fault and far-fault earthquakes show different story shear distribution due to the velocity pulse effect. The story shear distribution coefficient βi declines with seismic acceleration increasing. Besides, the proposed inelastic story shear models of D-HSS-EBFs have a better reflect the actual seismic response.